2020
DOI: 10.1007/s42421-020-00015-y
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Risk of Service Failures Between Successive Rail Inspections: A Data-Driven Approach

Abstract: Service failure is an incident when a defect of size over threshold value is noticed and the track is taken out of service. They are a major concern for the railroads due to their impact on economic and safety aspects of the rail company. Despite the effective inspection strategies developed by the railroad, service failure may still occur in their network because of the growth of an undetected defect or the defect that is initiated after an inspection. Various factors influence the growth rate of a defect, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Prediction of rail breaks will assist the railway companies to avoid possible derailments and to minimize the service interruptions caused by broken rails. In recent years, there has been a good attention to prediction of different types of rail defects for the purpose of railway maintenance using the recent advances in big data analytics (Ghofrani, Kumar, et al., 2020; Ghofrani, He, Mohammadi, Pathak, & Aref, 2019; Ghofrani, Pathak, Mohammadi, Aref, & He, 2020; Jamshidi et al., 2017; Mohammadi, He, Ghofrani, Pathak, & Aref, 2019). A comprehensive overview of all these studies could be found in Ghofrani, He, Goverde, and Liu (2018) and Ghofrani (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Prediction of rail breaks will assist the railway companies to avoid possible derailments and to minimize the service interruptions caused by broken rails. In recent years, there has been a good attention to prediction of different types of rail defects for the purpose of railway maintenance using the recent advances in big data analytics (Ghofrani, Kumar, et al., 2020; Ghofrani, He, Mohammadi, Pathak, & Aref, 2019; Ghofrani, Pathak, Mohammadi, Aref, & He, 2020; Jamshidi et al., 2017; Mohammadi, He, Ghofrani, Pathak, & Aref, 2019). A comprehensive overview of all these studies could be found in Ghofrani, He, Goverde, and Liu (2018) and Ghofrani (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Service failure is an incident when a defect of size over threshold value is noticed and the track is taken out of service (Ghofrani, Kumar, & Qing, 2020). Broken rails, as a major type of service failure, are a leading cause of derailments.…”
Section: Introductionmentioning
confidence: 99%
“…This has been the subject of numerous ongoing research activities using Weibull, Bayesian, and other probability models. 1018 It should be noted that many of the more recent probability models use a system probability approach to define risk of failure and associated derailments, while the Weibull approach is the one most commonly used to examine data on an individual segment basis.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al [3] employed the theory of Markov stochastic processes to estimate the rail break time in a long period, such as five years. A regression model based on survival analysis was developed by Ghofrani et al [4] to predict the risk of rail breaks between two successive rail inspections. Later, Ghofrani et al [5] developed an improved version of the prediction model to predict the arrival rate of rail breaks.…”
mentioning
confidence: 99%